The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4269/ajtmh.2012.11-0479
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Interferon-γ Levels and Leishmanin Skin Test Results in Persons Recovered for Leishmaniasis

Abstract: Abstract. Patients who recover from leishmaniasis usually show development of strong immunity and induction of interferon-γ (IFN-γ) and delayed type hypersensitivity. In a randomized trial, we analyzed the IFN-γ response by using a Quantiferon-Leishmania assay against three Leishmania peptide antigens and compared it with results of the leishmanin skin test (LST) in persons residing in areas in Iran to which zoonotic cutaneous leishmaniasis (ZCL, 181 persons), anthroponotic cutaneous leishmaniasis (ACL, 104 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The latter reported on an incremental increase in IFN-γ levels in cured individuals living in Northwest Ethiopia as compared to active patients but could not detect differences in IL-10 levels. Similar findings were reported in Turkish, Indian, Iranian, Spanish, and Bangladeshi VL patients [20,21,23,32,33], indicating a typical cellular hyporesponsiveness during active disease that restores after successful therapy, as was also reported in studies using peripheral blood mononuclear cell (PBMC). This was also reflected in the gradual increase in nonspecific PHA stimulation which suggests a broad mechanism of immunosuppression that merits further investigation.…”
Section: Discussionsupporting
confidence: 85%
“…The latter reported on an incremental increase in IFN-γ levels in cured individuals living in Northwest Ethiopia as compared to active patients but could not detect differences in IL-10 levels. Similar findings were reported in Turkish, Indian, Iranian, Spanish, and Bangladeshi VL patients [20,21,23,32,33], indicating a typical cellular hyporesponsiveness during active disease that restores after successful therapy, as was also reported in studies using peripheral blood mononuclear cell (PBMC). This was also reflected in the gradual increase in nonspecific PHA stimulation which suggests a broad mechanism of immunosuppression that merits further investigation.…”
Section: Discussionsupporting
confidence: 85%
“…There is evidence that when LST data are supported with information on the production of antigen-specific interferon-γ (IFN-γ), this could better assist in determining whether a suspected case has been exposed to a Leishmania infection [ 21 ]. In contrast, it is reported that the LST is significantly more sensitive than IFN-γ levels in persons who have been cured of CL [ 22 ].…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…The mean stimulation index values recorded after SLA challenge shows the cell-mediated immune response against Leishmania to be strongest in patients cured of VL. Differences in this response between patients cured of VL and CL have been reported previously, and might reflect a stronger systemic Th-1 response to occur in the former given the need to clear a much heavier parasite burden (Turgay et al, 2010 ; Alimohammadian et al, 2012 ). The patients with LLL—perhaps an evolved form of CL—showed the strongest immunological response before treatment, with Leishmania parasites present in affected lymph glands near the site of the Phlebotomus bite (Horrillo et al, 2015 ).…”
Section: Resultsmentioning
confidence: 64%